2020
DOI: 10.1186/s12909-020-02038-z
|View full text |Cite
|
Sign up to set email alerts
|

Using rapid cycle deliberate practice to improve primary and secondary survey in pediatric trauma

Abstract: Background Optimal performance of the primary and secondary survey is the foundation of Advance Trauma Life Support care. Despite its importance, not all primary surveys completed at level 1 pediatric trauma centers are performed according to established guidelines (Gala et al., Pediatr Emerg Care 32:756–762, 2016, Carter et al., Resuscitation 84:66–71, 2013). We hypothesize that rapid cycle deliberate practice (RCDP) will improve surgical residents’ confidence in performing the primary and secondary survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Another study showed an increase in knowledge gain in sepsis care in the pediatric population [22]. This strategy increased the trust of medical residents in their skills in providing pediatric trauma care [23]. Another trial showed increased performance related to human factors during pediatric resuscitation [8].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed an increase in knowledge gain in sepsis care in the pediatric population [22]. This strategy increased the trust of medical residents in their skills in providing pediatric trauma care [23]. Another trial showed increased performance related to human factors during pediatric resuscitation [8].…”
Section: Discussionmentioning
confidence: 99%
“…The individual case scenarios were created by principal investigator (D.H.Y.) 20 . All sessions were conducted using the Pediatric HAL S3005 mannequin on a hospital bed in the center of the pediatric trauma bay.…”
Section: Methodsmentioning
confidence: 99%
“…As awareness and experience with this method has increased over time, RCDP has become an instructional design element in an increasing number of resuscitation-related curriculums in recent years. [24] , [25] , [26] Originally, the essence of the RCDP instructional method was that the instructor intervenes when an error is noticed. However, others used RCDP by stopping the scenario only at the end cycle, [27] , [28] gave feedback at the end of the case and then re-run the scenario, 29 or allowed any learner to stop scenarios at any moment.…”
Section: Discussionmentioning
confidence: 99%